Analisis Faktor-Faktor yang Mempengaruhi Pelanggan Dalam Mengadopsi Teknologi Pompanisasi Listrik Melalui Program Electrifying Agriculture di PT PLN (Persero) UP3 Ponorogo - Dhani Kurniawan; Romauli Nainggolan (Journal of Economics and Management Scienties, 2026)
The transformation of energy in the agricultural sector has become a central agenda in enhancing efficiency and sustainability. PT PLN (Persero), through the Electrifying Agriculture (EA) program, aims to promote the adoption of electric pumps among farmers. However, adoption rates vary significantly, influenced by multiple factors that have not been comprehensively identified. This study examines the determinants of farmers’ adoption decisions using the Diffusion of Innovations (DOI) theory, which comprises five key dimensions: Relative Advantage, Compatibility, Complexity, Trialability, and Observability, with Intention as a mediating variable. A quantitative approach was applied using Structural Equation Modeling – Partial Least Squares (SEM-PLS) with a sample of 379 farmers in the PT PLN (Persero) UP3 Ponorogo service area, selected through purposive sampling. The findings indicate that Relative Advantage and Compatibility significantly and positively influence adoption intention, whereas Complexity has a negative impact. Trialability and Observability also contribute moderately to adoption decisions. Intention significantly mediates the relationship between all five DOI dimensions and adoption behavior. These results provide strategic recommendations for PT PLN (Persero) to enhance the effectiveness of the Electrifying Agriculture program.